2019
DOI: 10.1097/dcc.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Infection Control Course on Nursing Students' Knowledge of and Compliance With Universal Precautions

Abstract: Background Knowledge of and compliance with universal isolation precautions are important issues and were found to be low in many previous studies. However, there were no Jordanian studies that have examined the effect of an infection control teaching course on nursing students' knowledge of and compliance with universal precautions. Purpose This study aimed to assess knowledge and compliance levels, assess the relationships between knowledge and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 31 publications
0
24
0
3
Order By: Relevance
“…A study on nursing students in Hong Kong revealed good compliance with SPs, and better compliance was predicted by having good knowledge regarding SPs, lowly perceived barriers, sufficient training and supportive nursing staff and hospital management (Cheung et al, 2015). Another study in Oman reported that nursing students had poor knowledge of and compliance with SPs, and an IPC course significantly assisted the students in improving their knowledge and compliance (Tawalbeh, Al‐Rawajfah, & Habiballah, 2019). In Saudi Arabia, a multiuniversity study of nursing students presented that their highest compliance was in proper wearing of mask, whereas the poorest compliance was recorded in the disposal of sharps box before it is full.…”
Section: Introductionmentioning
confidence: 99%
“…A study on nursing students in Hong Kong revealed good compliance with SPs, and better compliance was predicted by having good knowledge regarding SPs, lowly perceived barriers, sufficient training and supportive nursing staff and hospital management (Cheung et al, 2015). Another study in Oman reported that nursing students had poor knowledge of and compliance with SPs, and an IPC course significantly assisted the students in improving their knowledge and compliance (Tawalbeh, Al‐Rawajfah, & Habiballah, 2019). In Saudi Arabia, a multiuniversity study of nursing students presented that their highest compliance was in proper wearing of mask, whereas the poorest compliance was recorded in the disposal of sharps box before it is full.…”
Section: Introductionmentioning
confidence: 99%
“…Among the senior practitioners, only 44% had received in-service training reflecting the need for additional efforts required in training them. Trainings on infection control are shown to increase the healthcare practitioner's knowledge compared to no interventions [14]. In our study, the participant's knowledge of the spread of hospital-acquired microorganisms was poor as the microbiology curriculum is not a part of their training.…”
Section: Discussionmentioning
confidence: 60%
“…is is receptivity for allopathic principles of infection control among the TM practitioners are an important avenue for intervention. Higher knowledge of infection control is linked with positive attitudes and higher compliance in practice [14,15]. As a part of the government's effort to prevent the spread of COVID-19 in Bhutan in 2020, all hospitals including the TMUs adopted infection prevention and control measures, and all health workers including TM practitioners were provided with training.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo experimental realizado na Jordânia com 60 alunos que participaram do curso online e 70 alunos do mesmo período que não participaram avaliou o nível de conhecimento dos alunos sobre precaução universal (Tawalbeh et al, 2019). De maneira geral baixos índices de conhecimento sobre controle de IRAS e sua aplicabilidade foram apresentados nos dois grupos antes da oferta do curso e após a oferta a avaliação do grupo experimental melhorou significativamente.…”
Section: Abordagemunclassified